Learn about taste and smell - Felicia, Law (UK : World Book, Inc.)
Poldy and his friends suddenly feel hungry. They land in the forest where Wagtail, Crow and Seagul find plenty of tasty food to eat.
Poldy
Keywords: Senses--Fiction; Children stories